2013
DOI: 10.1016/j.neubiorev.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Problems with measuring peripheral oxytocin: Can the data on oxytocin and human behavior be trusted?

Abstract: Research on the neurobiological and behavioral effects of oxytocin (OT), as well as on its possible therapeutic applications, has intensified in the past decade. Accurate determination of peripheral OT levels is essential to reach meaningful conclusions and to motivate, support and inform clinical interventions. Different, but concordant, methods for measuring plasma OT have been developed over the past four decades, but since 2004 several commercially available methods have been favored in research with human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
321
0
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(341 citation statements)
references
References 107 publications
8
321
0
6
Order By: Relevance
“…Divergent findings like these, whose clarification is pivotal for advancement of behavioral and psychiatric neuroendocrinology, may partly result from methodological heterogeneity, which leads to an issue of particular concern. Reliability and validity of widely-used commercially available immunoassays to quantify peripheral OT concentrations have been put into question (McCullough et al, 2013). Across studies, the reported peripheral OT concentrations are highly variable depending on the applied methods, with values ranging from < 10 to over 1200 pg/ml (Brandtzaeg et al, 2016; McCullough et al, 2013).…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%
See 1 more Smart Citation
“…Divergent findings like these, whose clarification is pivotal for advancement of behavioral and psychiatric neuroendocrinology, may partly result from methodological heterogeneity, which leads to an issue of particular concern. Reliability and validity of widely-used commercially available immunoassays to quantify peripheral OT concentrations have been put into question (McCullough et al, 2013). Across studies, the reported peripheral OT concentrations are highly variable depending on the applied methods, with values ranging from < 10 to over 1200 pg/ml (Brandtzaeg et al, 2016; McCullough et al, 2013).…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%
“…Reliability and validity of widely-used commercially available immunoassays to quantify peripheral OT concentrations have been put into question (McCullough et al, 2013). Across studies, the reported peripheral OT concentrations are highly variable depending on the applied methods, with values ranging from < 10 to over 1200 pg/ml (Brandtzaeg et al, 2016; McCullough et al, 2013). Thus, there is an urgent need to standardize OT assay protocols to guarantee high-quality research, which is indispensable for obtaining meaningful results as well as reliability and comparability between studies.…”
Section: Methodological Challenges Future Directions and Translatmentioning
confidence: 99%
“…On the other hand, other studies did detect oxytocin in the saliva of humans, including changes in that oxytocin after exposure to different behavioural paradigms 8, 9, 25. As stated in the introduction, these enzyme immunoassay‐based findings could be due to the cross‐reactivity of molecules other than oxytocin 12, but it is also possible that the detected molecules were indeed oxytocin from a central or even a local origin. The hypothalamus is not the only site that produces oxytocin molecules, as endothelial and epithelial cells at various other sites throughout the body have been reported to produce it 26.…”
Section: Discussionmentioning
confidence: 94%
“…Average collected saliva volumes in preterm infants are very small 10, and oxytocin may be broken down in saliva and thereby avoid detection by oxytocin‐specific antibodies used in commercially available enzyme immunoassays 11. Furthermore, the specificity of those antibodies allows detection of some other oxytocin‐like substances that can be misleading 12, especially when investigating the possibly very low concentrations of oxytocin in the saliva of preterm infants. We hypothesised that some of the barriers of measuring dynamic changes in oxytocin in the saliva of preterm infants could be overcome, by having a specialist laboratory perform a more sensitive radioimmunoassay 12 on the pooled saliva of multiple saliva collections before Kangaroo care and during Kangaroo care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation